2018
DOI: 10.11607/prd.3138
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Regenerative Treatment of Intrabony Defects in the Esthetic Zone Using Modified Vestibular Incision Subperiosteal Tunnel Access (M-VISTA)

Abstract: Periodontal regenerative treatment of intrabony defects in the esthetic zone often poses a significant challenge to clinicians. Various materials and techniques have been proposed to achieve periodontal regeneration. This article presents modified vestibular incision subperiosteal tunnel access (M-VISTA) for treatment of intrabony defects in the esthetic zone. Two cases were treated using the proposed approach with enamel matrix derivatives and demineralized freeze-dried bone allograft to optimize the regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Although techniques using an apical approach have been widely developed and used in mucogingival surgery with good results, [28][29][30] only a few preliminary studies describe the apical approach for periodontal reconstructive surgery. 20,31 Comparison of the two techniques showed no significant differences in PDr, but significant changes in CAG (P < 0.05), with more favorable results for the NIPSA group at 1 year. These results are due to a different response of the soft tissues (REC, TP, KT) according to the approach used.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although techniques using an apical approach have been widely developed and used in mucogingival surgery with good results, [28][29][30] only a few preliminary studies describe the apical approach for periodontal reconstructive surgery. 20,31 Comparison of the two techniques showed no significant differences in PDr, but significant changes in CAG (P < 0.05), with more favorable results for the NIPSA group at 1 year. These results are due to a different response of the soft tissues (REC, TP, KT) according to the approach used.…”
Section: Discussionmentioning
confidence: 94%
“…For NIPSA there is only one preliminary study, which showed results similar to the present ones. Although techniques using an apical approach have been widely developed and used in mucogingival surgery with good results, only a few preliminary studies describe the apical approach for periodontal reconstructive surgery …”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5]62 Therefore, it is not surprising that some authors have proposed the use of periodontal plastic surgery techniques when treating intrabony defects to maintain, or coronally advanced the level of the gingival margin. 3,4,[62][63][64] Zucchelli and De Sanctis proposed a modified approach for the treatment of intrabony defects (with EMD), that involved the use of an envelope coronally advanced flap, 3 as described previously in root coverage procedures. 65 The buccal flap was released, coronally advanced, and anchored to the defect's de-epithelialized adjacent papillae.…”
Section: Ta B L E 1 Strategies For Papilla Augmentation In Healthy Dentitionmentioning
confidence: 99%
“…63,68 Indeed, in a recent randomized controlled trial, the authors showed that the entire papilla preservation technique resulted in a 100% primary wound closure, with a significant CAL gain and a negligible increase in recession depth (0.2-0.36 mm). 69 Other approaches avoiding incisions at the level of the papilla have been described, such as the modified vestibular incision subperiosteal tunnel access (M-VISTA) 64 and the "non-incised papillae surgical approach" (NIPSA). 70 According to Moreno Rodriguez et al, the NIPSA achieved similar outcomes to a traditional minimally invasive papilla preservation technique, with a significantly lower recession at the tip of the interdental papilla (increased recession depth 0.2 versus 0.73 mm 1 year after, respectively).…”
Section: Ta B L E 1 Strategies For Papilla Augmentation In Healthy Dentitionmentioning
confidence: 99%
See 1 more Smart Citation